Understanding of guest behavioral intentions in peer-to-peer accommodation sector - Ye, Ye; Ali, Laiba; Foong, Yee Wong; Siew, Imm Ng; Lim, Xin-Jean (Frontiers Research Foundation, 2022)
The purpose of this study is to investigate the antecedents of guests’ behavioral intentions in Malaysia’s peer-to-peer (P2P) accommodation industry. This study focused on the effects of physical and social environment on guest emotions, satisfaction, and subsequently on guest’s behavioral intentions towards P2P accommodation. The proposed research framework was developed based on Stimulus-Organism-Response model. Partial Least Square Structural Equation Modeling (PLS-SEM) was used to examine the proposed hypotheses. Data were collected from 476 foreign visitors who stayed at P2P accommodations in Malaysia using online survey. The findings demonstrated that the P2P accommodation’s social and physical environment had a positive impact on guest satisfaction and emotions, while both satisfaction and emotions had significant impact on guest behavioral intentions. The findings also extend the applicability of the S-O-R theory in P2P accommodation context. In practice, both the physical and social environments are important stimuli cues to induce favorable level of organism factors, i.e., satisfaction and emotions. While behavioral intentions acted as the response factor in examining visitor’ responses towards P2P accommodation. All in all, this study emphasizes how crucial it is to emphasize on the external and internal factors when encouraging positive response in P2P accommodation platforms.